2022
DOI: 10.1108/jarhe-11-2021-0441
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of critical thinking and self-efficacy beliefs to teaching style preferences in higher education

Abstract: PurposeFollowing the significant role of critical thinking (CT), sense of efficacy beliefs and teaching style preferences in the success of teachers and consequently the success of the educational system, this study intended to explore their relationship and the possible influence of these three factors among English as a Foreign Language (EFL) university professors.Design/methodology/approachTo this end, Watson–Glaser Critical Thinking Appraisal-Form A, Teacher Sense of Efficacy Scale (TSES) and Grasha's Teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 65 publications
7
16
0
Order By: Relevance
“…They found that strong ER strategies played a significant role in decreasing teachers' emotional exhaustion and burn out. Furthermore, the gained findings lend support to those of Shen (2022), disclosing the mediator role of teacher ER in managing teachers' burnout, stress, and anxiety among English teachers.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…They found that strong ER strategies played a significant role in decreasing teachers' emotional exhaustion and burn out. Furthermore, the gained findings lend support to those of Shen (2022), disclosing the mediator role of teacher ER in managing teachers' burnout, stress, and anxiety among English teachers.…”
Section: Discussionsupporting
confidence: 64%
“…Their findings reflected those higher levels of work engagement and L2 grit immune EFL teachers in the face of different challenges during their professional lives. In a recent study in China, Li (2022) concluded that the relationship between EFL teachers' immunity, mindfulness, and work engagement was significantly positive. This study also necessitates the use of training courses for language teachers to enhance EFL teachers' immunity development, mindfulness, and engagement.…”
Section: Teacher Immunitymentioning
confidence: 99%
“…), and (3) efficacy in classroom management (e.g., How well can you implement alternative strategies in your classroom?). The reliability of the instrument was supported by the findings of Amirian et al (2022) . Based on the report of Cronbach’s alpha, the reliability of the TSES was acceptable (ranging from 0.756 to 0.891) in the current research.…”
Section: Methodsmentioning
confidence: 73%
“…Furthermore, teachers’ efficacy beliefs influence Students’ motivation, achievement, and efficacy ( Tschannen-Moran et al, 1998 ). From another perspective, it is evident that teachers’ self-efficacy predicts their attitude, teaching style, self-regulation, commitment, motivation, and effectiveness ( Barni et al, 2019 ; Fathi and Saeedian, 2020 ; Fathi et al, 2021 ; Heydarnejad et al, 2021a ; Amirian et al, 2022 ) and supports Students’ academic achievement ( Martin and Mulvihill, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation